Prostitution: what to punish? Workers, brothels, ruffians and customers (2019)
The present investigation analyzes the legal treatment of prostitution and its form of punishment when it is done coercively. From a Criminal Law perspective, there is some debate on whether it is necessary to expand the field of potential authors who, in